Counseling guidance methods in developing students’ morals at the Guppi Samata Gowa Islamic boarding school - Syamsidar, Syamsidar; Fadillah, Nur (Jurnal Mercusuar, 2020)
The guidance and counseling process is a process of developing the morals of students who are still searching for their identity, so that they do not make mistakes in taking action, by providing information services about good, correct, and targeted morals, in order to achieve the previously planned services. The Guidance and Counseling teacher, as the responsible party, must observe the students who will be given these services or guidance directly, so that the character and morals of the students can be formed according to the expected pattern.